Influence of socioeconomic and psychological factors in glycemic control in young children with type 1 diabetes mellitus - Carlos Jefferson do Nascimento Andrade; Crésio de Aragão Dantas Alves (Elsevier, 2019)
Objective: To evaluate the influence of socioeconomic and psychological factors on glycemic control in young children with type 1 diabetes mellitus. Methods: This was a cross-sectional study assessing prepubertal children with type 1 diabetes mellitus. The authors analyzed the socioeconomic status using the Brazil Economic Classification Criterion (Critério de Classificação Econômica Brasil [CCEB]) and psychological conditions through the Brazilian version of the Problem Areas in Diabetes, associated with glycemic control, measured by glycated hemoglobin (HbA1c). Descriptive analysis was used. The variables were assessed by bivariate and multivariate robust Poisson regression model, as well as Fisher's exact and Pearson's chi-squared tests to obtain the ratios of gross and adjusted prevalence ratio, with confidence interval being estimated at 95%. Results: A total of 68 children with type 1 diabetes mellitus were included in the study. A negative association between glycemic control (glycated hemoglobin levels), socioeconomic status (Brazil Economic Classification Criterion), and psychological condition (Brazilian version of the Problem Areas in Diabetes) was observed. Among the study participants, 73.5% (n = 50) of the children had an unfavorable socioeconomic status; these participants were 1.4 times more likely to present altered glycated hemoglobin values. In relation to individuals with compromised psychological status, 26 (38.2%) had a score above 70, thus being classified with psychological stress; these children were 1.68 times more likely (95% confidence interval: 1.101, 1.301) to have higher glycated hemoglobin levels. Conclusions: The socioeconomic conditions and psychological characteristics of the study participants were negatively associated with glycated hemoglobin results. These data reinforce the importance of the studied variables as predictors of glycemic control. Resumo: Objetivo: Avaliar a influência dos fatores socioeconômicos e psicológicos no controle glicêmico de crianças pequenas portadoras de diabetes mellitus tipo 1. Métodos: Estudo de corte transversal, avaliou crianças pré-púberes, com diabetes mellitus tipo 1. Foram analisados os fatores socioeconômicos com o Critério de Classificação Econômica Brasil e as condições psicológicas através da versão brasileira do Problem Areas in Diabetes (B-Paid), associado ao controle glicêmico, mensurado pela hemoglobina glicada. Foi utilizada análise descritiva. As variáveis foram avaliadas bivariada e multivariantemente pelo modelo de regressão de Poisson robusto, os testes Exato de Fisher e Qui-Quadrado de Pearson para as razões de prevalência bruta e ajustada, sendo o intervalo de confiança estimado em 95%. Resultados: Foram incluídas no estudo 68 crianças com diabetes mellitustipo 1. Foi observada uma associação negativa entre controle glicêmico (níveis de hemoglobina glicada), status socioeconômico (Critério de Classificação Econômica Brasil) e condição psicológica (versão brasileira do Problem Areas in Diabetes). Entre os participantes do estudo, 73,5% (n = 50) das crianças apresentaram status socioeconômico desfavorável, esses participantes apresentaram 1,4 vezes mais chances de apresentar valores alterados de hemoglobina glicada. Em relação a indivíduos com estado psicológico comprometido, houve uma prevalência de 26 (38,2%) apresentou uma pontuação acima de 70, sendo assim classificada com estresse psicológico, essas crianças foram 1,68 vezes mais prováveis (intervalo de confiança 95%: 1,101, 1,301) de apresentar níveis mais elevados de hemoglobina glicada. Conclusão: As condições socioeconômicas e as características psicológicas dos participantes do estudo foram negativamente associadas aos resultados da hemoglobina glicada. Esses dados reforçam a importância das variáveis estudadas como preditores de controle glicêmico. Keywords: Child, Type 1 diabetes mellitus, Glycemia, Socioeconomic factors, Psychological stress, Palavras-chave: Criança, Diabetes mellitus tipo 1, Glicemia, Fatores socioeconômicos, Estresse psicológico